1-Aryl-F-1,3-butadienes and Unsymmetrical alpha,omega-Diaryl-F-polyenes - Shtarev, Alexander B.; Kremlev, Mikhail M.; Chvátal, Zdenek (The Journal of organic chemistry, 1997)
Para-substituted 1-aryl-F-1,3-butadiene derivatives p-R-C(6)H(4)-CF=CFCF=CF(2) (2a-g), where R = H, CH(3), OCH(3), OC(6)H(11), N(CH(3))(2), Br, and CF(3), have been prepared by reaction of appropriate arylmagnesium bromides with F-1,3-butadiene. (19)F NMR chemical shifts correlate with sigma(p) Hammett substituent constants. Compounds 2a-e react on their terminal perfluorovinyl group with C-nucleophiles and were used as intermediates in subsequent reactions with suitable organolithium compounds for the synthesis of a new series of unsymmetrically substituted alpha,omega-diaryl-F-polyenes RC(6)H(4)(CF=CF)(n)()C(6)H(4)R', where n = 2 or 3 and R' is one of the substituents specified above. A variety of new synthons containing alpha,omega-diaryl-F-1,3-butadiene skeleton and reactive Br, OH, CH=O, and COOH functionalities in para-positions on aromatic rings has been also prepared. Structural aspects, NMR spectra, and mesogenic properties of the title compounds are discussed.